Examining the Influences of Psychosocial Factors on Delinquent Behav-iours in the Agona West Municipality - Nyarko, Benjamin; Braimah, Mary; Kamilu, Abdulai Mohammed (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
Delinquent behaviours of adolescents have become a major issue of concern to many countries in the world. The purpose of this study was to find out the influence of psychosocial factors on delinquent behaviours of adolescents. Using a descriptive survey design and a proportionate sampling technique, a total of 327 form two Senior High School students (SHS) were drawn from Nyakrom SHS, Siddique SHS, Fankoba SHS and Swedru School of Business to participate in the study. A 45-item questionnaire with a reliability coefficient 0.72 was adopted for data collection. The study was guided by a research question and hypothesis. Mean and standard deviation were used to analyse data on the research question whilst multiple regression analysis was used to analyse data on the hypothesis. The study revealed that psychosocial factors such as the school, peers and the family were responsible for influencing delinquent behaviours of adolescents. To help curb delinquent behaviours among adolescents, the study recommended that adolescent students should be vigorously sensitized by school counsellors, headmasters and teachers on some psychosocial factors that can easily lead them to engage in delinquent behaviours.